New differential cryptanalysis results for the lightweight block cipher BORON - Teh J.S.; Tham L.J.; Jamil N.; Yap W.-S. (Elsevier Ltd, 2023)
Cryptography; Gears; Probability; Security of data; Branch and bounds; Cryptanalyse; Differential characteristic; Differential cryptanalysis; Key models; Key recovery attacks; Lightweight block ciphers; Secret key; SMT solv; Substitution-permutation networks; Boron